"Where's My Choice?" An Examination of Veteran and Provider Experiences With Hepatitis C Treatment Through the Veteran Affairs Choice Program. (July 2017) - Tsai, Jack; Yakovchenko, Vera; Jones, Natalie; Skolnik, Avy; Noska, Amanda; Gifford, Allen L.; McInnes, D. Keith
Abstract : Background: The Department of Veterans Affairs (VA) is the country's largest provider for chronic hepatitis C virus (HCV) infection. The VA created the Choice Program, which allows eligible veterans to seek care from community providers, who are reimbursed by the VA. Objectives: This study aimed to examine perspectives and experiences with the VA Choice Program among veteran patients and their HCV providers. Research Design: Qualitative study based on semistructured interviews with veteran patients and VA providers. Interview transcripts were analyzed using rapid assessment procedures based in grounded theory. Subjects: A total of 38 veterans and 10 VA providers involved in HCV treatment across 3 VA medical centers were interviewed. Measures: Veterans and providers were asked open-ended questions about their experiences with HCV treatment in the VA and through the Choice Program, including barriers and facilitators to treatment access and completion. Results: Four themes were identified: (1) there were difficulties in enrollment, ongoing support, and billing with third-party administrators; (2) veterans experienced a lack of choice in location of treatment; (3) fragmented care led to coordination challenges between VA and community providers; and (4) VA providers expressed reservations about sending veterans to community providers. Conclusions: The Choice Program has the potential to increase veteran access to HCV treatment, but veterans and VA providers have described substantial problems in the initial years of the program. Enhancing care coordination, incorporating shared decision-making, and establishing a wide network of community providers may be important areas for further development in designing community-based specialist services for needy veterans. Abstract : Supplemental Digital Content is available in the text.